Gulf Cooperation Council countries' water and climate research to strengthen UN's SDGs 6 and 13. Issue 3 (March 2023) - Sherif, Mohsen; Abrar, Muhammad; Baig, Faisal; Kabeer, Saifudeen
Abstract: Clean water and sanitation and climate actions represent two of the seventeen United Nations Sustainable Development Goals (SDGs). Although challenging, the two goals can be achieved by 2030 through unconventional and innovative solutions. Scientific research related to clean water and sanitation (SDG 6) and urgent actions to combat climate change and its impacts (SDG 13) will help develop new technologies to support the two goals and can bridge the gap between practitioners and academia's to achieve sustainability. The Gulf Cooperation Council (GCC) countries are located in an arid region. Their water and climate research activities and outcomes may provide a good contribution toward achieving the two goals. This study used text mining and bibliometric methods to analyze water and climate research contributions to achieve SDGs 6 and 13 in GCC countries. Results revealed that there is an increase in research publications after 2016 in the areas of water and climate in the GCC countries involving a longstanding international collaboration with developed countries. Research topics were focused on wastewater treatment, contamination, heavy metal, groundwater, and climate change impacts. Under SDG 6, most of the publications were research articles (77.3%), followed by reviews (11.1%), and the rest were book chapters and conference papers. For SDG 13, 75.1% of the publications are research articles, 10.9% are conference papers, and 8% are reviews. The research outcomes in the GCC countries have clearly contributed to the development of water and climate strategies and international collaborations to achieve the two goals.